Advancing bone tissue engineering: anisotropic performance of poly(lactic-co-glycolic acid) (PLGA) composites with nano-calcium sulphate (nCS) and fucoidan (fu) - Ab Ghani, Norshazliza; Abdul Kadir, Mohammed Rafiq; Maran, Sathiya; Kamal, Izdihar; Abdul Karim, Muhammad Khalis; Mohd Zaid, Mohd Hafiz; Raghavendran, Hanumanth Rao Balaji; Ramlee, Muhammad Hanif; Tunku Kamarul Zaman, .; Ammarullah, Muhammad Imam (Taylor and Francis, 2026)
This study investigates the anisotropic properties of three different poly(lactic-co-glycolic acid) (PLGA)-based materials: PLGA with nano-calcium sulphate (nCS), PLGA with fucoidan (fu) and PLGA with both nCS and fu. Using finite element analysis (FEA), the study explores their potential applications in bone tissue engineering. Anisotropy, or the directional dependency of mechanical properties, is critical in designing biomaterials for bone regeneration due to the complex, hierarchical structure of natural bone. The objective was to evaluate the mechanical behaviour of each composite material under simulated physiological conditions, focusing on their anisotropic responses to loading. The findings indicate that PLGA-nCS exhibited the highest degree of anisotropy, with enhanced stiffness and strength along preferred load-bearing directions, making it suitable for applications requiring higher mechanical stability. In contrast, PLGA-nCS-fu demonstrated moderate mechanical strength but displayed isotropic behaviour, ensuring consistent compressive performance across all directions. The study highlights the synergistic effects of incorporating nCS and fu into PLGA-based materials. fu, a natural sulphated polysaccharide derived from brown seaweed, significantly enhances the biological performance of these composites.